Strategic agenda for Caribbean policy towards the new U.S. government : policy report (Manchester Trade Ltd. WashingtonUS, 2001)
Seeks to provide an analytical basis of the new Bush administration upon which policy initiatives can be developed. Indicates and identifies areas of challenges and opportunities for CARICOM under the Bush administration.
Keywords: FOREIGN RELATIONS